Work Area Layout Optimization Using the BLOCPLAN Method: Optimalisasi Tata Letak Area Kerja Menggunakan Metode BLOCPLAN - Najmuddin Syah, Mochammad Dhia; Rusindiyanto (Indonesian Journal of Innovation Studies, 2025)
The automotive sector in Indonesia has experienced consistent growth, not only in production and sales but also in after-sales services such as body repair. At PT. Putra Jawamas, inefficiencies in the workshop facility layout hinder optimal service delivery. A knowledge gap exists in leveraging both qualitative and quantitative tools for facility redesign in such settings. This study aims to improve the layout of PT. Putra Jawamas’ body repair area using the BLOCPLAN method, supported by Activity Relationship Chart (ARC) and From-To Chart (FTC) analysis. The results generated 20 layout alternatives, from which Layout B—with the highest adjacency score (0.83) and lowest rel-dist score (0.77)—was selected as optimal. The novelty lies in integrating ARC with FTC metrics to reinforce layout selection decisions. The implications of this redesign include reduced material handling distances, enhanced workflow efficiency, and increased service capacity. This study demonstrates that combining ARC and FTC in the BLOCPLAN framework provides a robust methodology for facility layout optimization in service-oriented automotive workshops.Highlight : The study applies the BLOCPLAN method to redesign the layout at PT. Putra Jawamas, aiming to improve operational efficiency in body repair services. Layout B was chosen as optimal with the highest Adjacency Score (0.83) and a low Rel-Dist Score (0.77), indicating better spatial relationships and reduced movement. Combining ARC and FTC data helped refine layout choices and justify the proposed reconfiguration for maximum productivity. Keywords : Facility Layout, BLOCPLAN, Activity Relationship Chart, Adjacency Score, Rel-Dist Score